Stamped Rhodian Amphorae in the Güray Museum: New Eponym-Fabricant Associations - Burcu Tüysüz; Gonca Şenol; Erkan Alkaç (Gephyra)
Stamped amphorae and their stamps on them have been the subject of scientific studies for more than a century, and the stamped amphorae found in both archaeological excavations and museum collections have been evaluated and brought to the literature. The three complete stamped Rhodian amphorae registered in the Güray Museum inventory are the subject of this study. The aim of the study is to date the amphorae and to determine the eponyms and fabricants on the stamps on their handles. In this study, on the first amphora, the eponym Aratophanes I and the month Artamitios and the fabricant Aristokles II; on the second the eponym Aleximachos and the month Thesmophorios and the fabricant Bromios; on the last one, the eponym Timodikos and the month Sminthios and the fabricant Nysios were detected together. In this study, new eponym-fabricant associations, which were not previously identified, were detected and the use of fabricant and eponym matrices/dies together was revealed. Thus, new contributions have been made to the understanding of the Rhodian amphora stamping system and its chronology.